Progressive Islamic Teaching and Learning: Integrating Knowledge and Practice for Societal Advancement - Dzulfikar Akbar Romadlon; Istikomah Istikomah; Budi Haryanto (Indonesian Journal of Cultural and Community Development, 2023)
This conceptual study explores the paradigm of progressive Islamic teaching and learning, addressing the disconnection between traditional teachings and modern science, which hinders their societal relevance. Fueled by the "progressive Islam" paradigm initiated by Muhammadiyah, this research advocates for integrating Islamic doctrines and practices with scientific knowledge to enhance individual and societal well-being. Employing a conceptual survey, the study analyzes existing literature to propose that modern teaching methods should be employed to facilitate a deeper understanding, practical application, and reflection of Islamic teachings. The study's implications underline the significance of fostering a harmonious integration between Islamic education and modern knowledge, contributing to the advancement of both individual growth and social progress. Highlight: Societal Disconnection Addressed: This study explores the paradigm of progressive Islamic teaching, bridging the gap between traditional teachings and modern science, crucial for enhancing societal relevance. Integration for Well-being: Fueled by the "progressive Islam" paradigm, the research advocates for merging Islamic doctrines and practices with scientific knowledge to bolster individual and societal well-being. Modernization of Education: Through a conceptual survey, the study emphasizes the importance of utilizing contemporary teaching methods to enable a comprehensive grasp, practical implementation, and thoughtful contemplation of Islamic teachings, thereby contributing to individual growth and societal advancement. Keyword: Progressive Islamic Teaching, Modern Science, Societal Relevance, Integrating Knowledge, Teaching Methods